Adapting the protocol for Narrative Exposure Therapy for adults with mild intellectual disabilities - Marlow, Katie (2021)
Background: The rise of trauma-informed care in health services in the UK has highlighted the need for patients to receive care that considers trauma and includes referral for trauma-focused treatment where appropriate (Sweeney et al., 2016). Adults with Intellectual Disabilities (ID) are more vulnerable to developing post-traumatic stress disorder (PTSD) than the general population (Fletcher et al., 2016), however, research exploring effective trauma-focused therapies within this population is limited. Narrative Exposure Therapy (NET; Schauer et al., 2011) is recommended by the National Institute for Health and Care Excellence (2018) to treat PTSD in adults. There is a lack of research exploring firstly, the effectiveness of NET among adults with ID and secondly, what adaptations are required for this population.